EFFECTIVENESS OF PRE-ROLL ADS ON YOUTUBE TO CONSUMER PURCHASE INTENTION - Pangihutan, Yehezkiel; Fachira, Ira (Journal of Business and Management, 2018)
Abstract.YouTube provides new ways for companies to promote their products. From banner, pre-roll ads, and poster. Companies see this chance because numbers of YouTube uers are increasing rapidly in Indonesia. The users itself conclude to publisher, subscriber, and watcher too. But, the problem is there is limited studies about the effectiveness of YouTube ads toward the audience’s purchase intention. The aim of this study is to investigate the pre-roll ads on YouTube effect the audiences purchase intention. It is important because there’s so much advertisers that put their ads in this platform, but we don’t know about it’s effectivity to their purchase intention. The pruchase intention itself is useful for their sales. The advertisement used are advertisement in scope YouTube Indonesia and the product that exist in Indonesia market. The sample of this research is an internet user who lives in Indonesia. The questionnaire distributed through social media and then analyzed using Structure Equation Modeling (SEM). With SEM we can be able to provide analysis if the dependent variable is more than one.Findings show that pre-roll ads positively and significantly effect their audiences purchase intention. Therefore, using application pre-roll ads on YouTube for advertising really should be considered due to good impact.Keywords : advertisement, purchase intention, pre-roll ads, YouTube